CHUVASH LOAN WORDS IN THE DIALECTS OF THE KRESHIN TATARS - Aniferova, Violetta Vitalyevna; Kirillova, Zoya Nikolaevna; Alkaya, Ercan (Unesp-Faculdade Ciencias & Letras, 2021)
The article is intended to show the relations between Tatar and Chuvash and to examine Chuvash loan words in the dialect of Kreshin Tatar, which is a specific group of Tatar people. Tatars and Chuvash, who have lived as neighbors for a long time, not only have economic and daily relations, but also a mutual language influence, as a result of which mutual loans are exchanged between them. The paper also approaches the tight links between the two peoples and some language relations. Chuvash loans are present in the various aspects of daily life of the dialect of Melki Kreshins, for example, tundi kin (Monday), utlari kin (Tuesday), kekey (meat), kuksa (skinhead), kirsut (house fairy), cikres (twin), capli (good, beautiful), etc. to be compared with their Chuvash parallels, in terms of usage features. In addition, the dresses of girls and women of Melki Kreshins, which are accepted as Chuvash dresses, but whose names are not taken from Chuvash, such as takiya (women's headdress, decorated with bright stones and scales, fez), tastar (hijab made of white linen weave), tastar yawligi (tastar hijab), kaspaw (round cap decorated with scales that used to be worn by women), etc. which will be examined on the basis of their equivalent in Tatar, Chuvash and other dialects.
Keywords: Tatars; Chuvashes; Kreshin tatars; Dialects; Chuvash loans